Instrument and automation engineers' handbook. Volume II, - Lipták, Béla G.; Venczel, Kriszta (Taylor & Francis, CRC Press, 2017)
The Instrument and Automation Engineers' Handbook (IAEH) is the #1 process automation handbook in the world. Volume two of the Fifth Edition, Analysis and Analyzers, describes the measurement of such analytical properties as composition. Analysis and Analyzersis an invaluable resource that describes the availability, features, capabilities, and selection of analyzers used for determining the quality and compositions of liquid, gas, and solid products in many processing industries. It is the first time that a separate volume is devoted to analyzers in the IAEH. This is because, by converting the handbook into an international one, the coverage of analyzers has almost doubled since the last edition. Analysis and Analyzers:Discusses the advantages and disadvantages of various process analyzer designsOffers application- and method-specific guidance for choosing the best analyzerProvides tables of analyzer capabilities and other practical information at a glanceContains detailed descriptions of domestic and overseas products, their features, capabilities, and suppliers, including suppliers' web addressesComplete with 82 alphabetized chapters and a thorough index for quick access to specific information, Analysis and Analyzersis a must-have reference for instrument and automation engineers working in the chemical, oil/gas, pharmaceutical, pollution, energy, plastics, paper, wastewater, food, etc. industries. About the eBookThe most important new feature of the IAEH, Fifth Editionis its availability as an eBook. The eBook provides the same content as the print edition, with the addition of thousands of web addresses so that readers can reach suppliers or reference books and articles on the hundreds of topics covered in the handbook. This feature includes a complete bidders' list that allows readers to issue their specifications for competitive bids from any or all potential product suppliers.